Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's fill in the table step-by-step by substituting each value of [tex]\( x \)[/tex] into the given quadratic function [tex]\( y = 2x^2 - 3x + 1 \)[/tex].
We start with the general formula:
[tex]\[ y = 2x^2 - 3x + 1 \][/tex]
1. For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = 2(1)^2 - 3(1) + 1 = 2 - 3 + 1 = 0 \][/tex]
So, when [tex]\( x = 1 \)[/tex], [tex]\( y = 0 \)[/tex].
2. For [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 2(0)^2 - 3(0) + 1 = 0 - 0 + 1 = 1 \][/tex]
So, when [tex]\( x = 0 \)[/tex], [tex]\( y = 1 \)[/tex].
3. For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = 2(-1)^2 - 3(-1) + 1 = 2(1) + 3 + 1 = 2 + 3 + 1 = 6 \][/tex]
So, when [tex]\( x = -1 \)[/tex], [tex]\( y = 6 \)[/tex].
4. For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 2(2)^2 - 3(2) + 1 = 2(4) - 6 + 1 = 8 - 6 + 1 = 3 \][/tex]
So, when [tex]\( x = 2 \)[/tex], [tex]\( y = 3 \)[/tex].
Now, filling in these values into the table, we get:
[tex]\[ \begin{tabular}{|c|c|} \hline x & y \\ \hline 1 & 0 \\ \hline 0 & 1 \\ \hline -1 & 6 \\ \hline 2 & 3 \\ \hline \end{tabular} \][/tex]
So the completed table is:
[tex]\[ \begin{tabular}{|c|c|} \hline x & y \\ \hline 1 & 0 \\ \hline 0 & 1 \\ \hline -1 & 6 \\ \hline 2 & 3 \\ \hline \end{tabular} \][/tex]
We start with the general formula:
[tex]\[ y = 2x^2 - 3x + 1 \][/tex]
1. For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = 2(1)^2 - 3(1) + 1 = 2 - 3 + 1 = 0 \][/tex]
So, when [tex]\( x = 1 \)[/tex], [tex]\( y = 0 \)[/tex].
2. For [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 2(0)^2 - 3(0) + 1 = 0 - 0 + 1 = 1 \][/tex]
So, when [tex]\( x = 0 \)[/tex], [tex]\( y = 1 \)[/tex].
3. For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = 2(-1)^2 - 3(-1) + 1 = 2(1) + 3 + 1 = 2 + 3 + 1 = 6 \][/tex]
So, when [tex]\( x = -1 \)[/tex], [tex]\( y = 6 \)[/tex].
4. For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 2(2)^2 - 3(2) + 1 = 2(4) - 6 + 1 = 8 - 6 + 1 = 3 \][/tex]
So, when [tex]\( x = 2 \)[/tex], [tex]\( y = 3 \)[/tex].
Now, filling in these values into the table, we get:
[tex]\[ \begin{tabular}{|c|c|} \hline x & y \\ \hline 1 & 0 \\ \hline 0 & 1 \\ \hline -1 & 6 \\ \hline 2 & 3 \\ \hline \end{tabular} \][/tex]
So the completed table is:
[tex]\[ \begin{tabular}{|c|c|} \hline x & y \\ \hline 1 & 0 \\ \hline 0 & 1 \\ \hline -1 & 6 \\ \hline 2 & 3 \\ \hline \end{tabular} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.